PENGARUH KUALITAS SISTEM INFORMASI AKADEMIK MAHASISWA TERHADAP KEPUASAN MAHASISWA STT INDONESIA TANJUNGPINANG - Muhammad Taufik Syastra (Universitas Putera Batam, 2013)
Quality of Student Academic Information Systems need to be considered to improve user satisfaction, which in this study users of academic information systems students are students of Indonesian STT Tanjungpinang. Student academic information system applied to the STT Indonesia in support of student academic data processing, such as KRS (Study Plan Card), KHS (Card Study Results), and so forth. Students from Indonesia amounted to as much as 475 STT students, using simple random sampling technique and precision Yamane formula taro 10%, then obtained a sample of 83 students. This study uses verification, which verifies the influence of Quality Information System (independent variable) on student satisfaction (dependent variable). The results of this study were (1) There is an effect between the quality system of student academic information system to student satisfaction, (2) There is the influence of the quality of information on students 'academic information system to student satisfaction, (3) There is the influence of the quality of students' academic information system student satisfaction.